Stock Portfolio Excess Returns and Macroeconomic Variables: An Empirical Analysis of the Singapore Stock Market - Ariff, Mohamed (Institutional Knowledge at Singapore Management University, 1990)
Economic agents use information in forming their expectations of future returns from holding stock securities. These securities should be priced to reflect the risks due to economywide fluctuations. The information is updated given the realisations of the factors, which are taken as unobservable but that affect the utility of possibly risk-averse agents. Stock portfolio excess returns (or risk premiums) are analysed empirically within the framework of the Dynamic Factor Model which allows for serial correlation in the factors. Over the sample period 1975:1 to 1986 (January 1975 to June 1986), a single factor can parsimoniously represent ten stock portfolio excess returns. In the framework of the Dymimic model, causality tests for several macroeconomic variables are carried out to ascertain if these variables are correlated with the stock portfolio excess returns. The finding that the excess returns are correlated with the variables that enter the causal equations with a lag is consistent with the conjecture that these variables are used by economic agents in forming their expectations of future treasury security excess returns or risk premiums. Variables possibly related to real activities in the economy are not rejected as causal variables.